Alternative methods in toxicology: CFU assays application, limitation and future prospective. (2nd January 2016) - Yadav, Navneet Kumar; Shukla, Pooja; Omer, Ankur; Singh, Poonam; Singh, R. K.
Abstract: Blood is a fluid connective tissue which plays a vital role for normal body function. It consist different type of blood cells which is continuously reproduce inside the bone marrow from hematopoietic system. Xenobiotics could be specifically toxic to the hematopoietic system and they can cause hematological disorders by disturbing the normal functions. In vitro hematopoietic colony-forming cell assays play a crucial role to evaluate potential toxic effects of new xenobiotics and also helpful in bridging the gap between preclinical toxicology studies in animal models and clinical investigations. Use of these assays in conjunction with, high-throughput screening reduces the cost and time associated with these assays. This article provides a critical view over in vitro hematopoietic colony-forming cell assays in assessment of hematotoxicity.